Penanaman Morality Goodness Pada Anak melalui Metode Mendongeng Kisah Nabi Muhammad saw - mujib, Ana lailatul maghfiroh (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Religious values are life values that reflect the growth and development of religious life which consists of three main elements, namely aqidah, worship and morals which serve as guidelines for behavior in accordance with divine rules. One-way teachers instill religious and moral values is by using the storytelling method.  Therefore, the teacher took the initiative to instill this through the storytelling method using serial picture story books. This research aims to instill religious and moral values through the Storytelling Method in group B aged 5-6 years. This research uses a qualitative approach with descriptive research type.  Data collection techniques in this research used observation, interviews and documentation.  Data analysis uses data collection, data condensation, data presentation and drawing conclusions.  Meanwhile, data validity uses triangulation of techniques and sources. Based on the findings and discussion in the research that has been carried out, it can be concluded that instilling Morality Goodness in early childhood through the method of telling the story of the Prophet Muhammad SAW is carried out in 3 stages, namely: preparation stage, implementation stage, and learning evaluation stage.  The obstacles for educators in instilling Morality Goodness in early childhood through the method of telling the story of the Prophet Muhammad SAW are: The condition of parents who pay little attention to children's activities and lack of parental knowledge of children's needs, habits or tasks at home which is not in line with habits at school, lack of media and infrastructure.